Pro Dan Kontra Terhadap Perspektif Gender Dalam Undang-Undang No.1 Tahtjn 1974 Tentang Perkawinan - . Ermasyanti (KEADILAN PROGRESIF, 2011)
The pro and contra towards gender perspective in Marriage law No.1 year 1974, there two perspective, is : 1) contra perspective, wife in domestic area and husband presents in public area, this wisdom doesnâtÂ  give justice, puhes woman improverishment process. In Marriage law found discrimination towards woman should be abolished, with be ratified woman be Law No. 7 year 1984 about Discrimination, Abolition Towards Woman, so that, necessary right formulation revision and spouse duty in marriage law. Pro perspective, marriage laws correct and unnecessary at revision because right and duty must not be interpretted corred but be seen based on moral and the philosophy. The marriage is pray, hoppy family must basd on affection, mutual respect,love to love and mutual give good aid borns and mind. Task situating and responsibility must be discriminated by harmonization and symmetrical so that firm and shoulderred with responsibility .